Juvenile Laryngeal Papillomatosis - Coope, Gerald (Prim Care Respir J, 2006)
Always ask about hoarseness and quality of voice in a history of any child presenting with cough or asthma-like symptoms. Children presenting with what appears to be an acute onset of hoarseness, without any physical signs of airways obstruction, should be reviewed after two weeks. If there is chronic hoarseness, referral to an ENT specialist should be considered with a view to laryngoscopy. If the child develops clinical signs of acute airway obstruction such as stridor or respiratory distress, prompt paediatric review is indicated. When referring, it is important to emphasise whether or not there is chronic hoarseness in order to differentiate the diagnosis from croup. Juvenile Laryngeal Papillomatosis may present with cough, pneumonia, dysphagia, or stridor, as well as hoarseness. These patients are often misdiagnosed as having asthma or allergies.